Development of a Control and Monitoring System for an IoT Rover Based on ESP32 and LoRa in Hazardous Areas - Ananda, Naufal Choirul; Maulindar, Joni; Ardiyanto, Marta (Politeknik Negeri Lhokseumawe, 2025)
This study developed a control and monitoring system for an IoT-based rover using ESP32 and LoRa, designed for hazardous area exploration. The system integrates two wireless communication methods: LoRa for long-range sensor data transmission and NRF24L01 for real-time control. The MQ-6 sensor detects LPG gas, while ultrasonic sensors function as an automatic safety system. A web-based interface built with Next.js and Supabase displays real-time sensor data. The system was developed using a prototyping method that includes requirement analysis, system design, hardware and software development, and testing. Test results show that LoRa transmits data reliably up to 15 meters without obstructions, and NRF24L01 supports stable control up to 100 meters. The MQ-6 sensor accurately detects gas presence, and ultrasonic sensors consistently stop the rover when obstacles are detected within 30 cm. The monitoring website successfully presents real-time data for operator decision-making. Overall, the system is effective and responsive for remote operation in high-risk environments, with strong potential for deployment in scenarios such as gas leaks, disaster zones, or other dangerous areas.